2009
DOI: 10.4049/jimmunol.0900152
|View full text |Cite
|
Sign up to set email alerts
|

The Gli3 Transcription Factor Expressed in the Thymus Stroma Controls Thymocyte Negative Selection Via Hedgehog-Dependent and -Independent Mechanisms

Abstract: The Hedgehog (Hh) responsive transcription factor Gli3 is required for efficient thymocyte development in the fetus. In this study we show that Gli3, not detected in adult thymocytes, is expressed in the murine fetal and adult thymus stroma. PCR array analysis revealed Cxcl9, Rbp1, and Nos2 as novel target genes of Gli3. We show that Gli3 positively regulates the expression of these genes, most likely by suppressing an intermediate repressor. Deletion of autoreactive thymocytes depends on their interactions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
46
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 58 publications
6
46
0
Order By: Relevance
“…It may also differ from the function of other components involved in canonical Hh signaling. Examples are Hh, which was reported to activate or inhibit intrathymic T cell proliferation and differentiation in a dose-dependent manner (2,3), and Gli2 and Gli3, which were shown to influence, for example, TCR repertoire selection (8,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may also differ from the function of other components involved in canonical Hh signaling. Examples are Hh, which was reported to activate or inhibit intrathymic T cell proliferation and differentiation in a dose-dependent manner (2,3), and Gli2 and Gli3, which were shown to influence, for example, TCR repertoire selection (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that all major components of the Hhsignaling cascade (e.g., Hh, Ptch, Smo, and Gli) are important for T cell development (2)(3)(4)(5)(6)(7)(8)(9). In the thymus, Hh is produced by the thymic stroma, where Ptch and its signaling partner Smo are expressed (2,6).…”
mentioning
confidence: 99%
“…Transcription factors, such as Th-POK, play essential roles in lineage commitment, and the ways in which the transcriptional regulation of lineage commitment relate to TCR signaling require further study [11]. In addition, other secreted factors from TEC, such as the morphogen Sonic hedgehog influence TCR repertoire selection and differentiation from DP to SP cell [13,14].…”
Section: A Very Brief Overview Of T Cell Developmentmentioning
confidence: 99%
“…Knockout (KO) and transgenic mouse models show that Hh signaling regulates thymocyte development (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Peripheral T cells express components of the Hh signaling pathway (15), which is involved in regulation of T cell activation in vitro (11,12,15,16).…”
mentioning
confidence: 99%